Celastrol ameliorates liver metabolic damage caused by a high-fat diet through Sirt1 - Yinliang Zhang; Chao Geng; Xiaoyan Liu; Meixia Li; Mingyue Gao; Xiaojun Liu; Fude Fang; Yongsheng Chang (Elsevier, 2017)
Objective: Celastrol was recently identified as a potential novel treatment for obesity. However, the effect of Celastrol on nonalcoholic fatty liver disease (NAFLD) remains elusive. The aim of this study is to evaluate the role of Celastrol in NAFLD. Methods: Functional studies were performed using wild-type C57BL/6J (WT) mice and liver specific Sirt1-deficient (LKO) mice. The molecular mechanism was explored in primary mouse liver and primary hepatocytes. Results: When WT mice receiving a high-fat diet (HFD) were treated with Celastrol, reductions in body weight, subcutaneous and visceral fat content, and liver lipid droplet formation were observed, along with reduced hepatic intracellular triglyceride and serum triglyceride, free fatty acid, and ALT concentrations. Furthermore, Celastrol decreased hepatic sterol regulatory element binding protein 1c (Srebp-1c) expression, enhanced the phosphorylation of hepatic AMP-activated protein kinase α (AMPKα), and increased the expression of hepatic serine-threonine liver kinase B1 (LKB1). Additionally, Celastrol treatment improved glucose tolerance and insulin sensitivity in WT mice fed the HFD. Celastrol administration also improved the anti-inflammatory and anti-oxidative status by inhibiting nuclear factor kappa B (NFκB) activity and the mRNA levels of proinflammatory cytokines and increasing mitochondrial DNA copy number and anti-oxidative stress genes expression in WT mice liver, in vivo and in vitro. Moreover, Celastrol induced hepatic Sirt1 expression in WT mice, in vivo and in vitro. These Celastrol-mediated protective effects in WT mice fed a HFD were abolished in LKO mice fed a HFD. It was more interesting that Celastrol aggravated HFD-induced liver damage in LKO mice fed a HFD by inhibiting the phosphorylation of AMPKα and boosting the translocation of NFκB into the nucleus, thereby resulting in the increase of Srebp-1c expression and the mRNA levels of liver proinflammatory cytokines. Conclusions: Celastrol ameliorates NAFLD by decreasing lipid synthesis and improving the anti-oxidative and anti-inflammatory status. And Sirt1 has an important role in Celastrol-ameliorating liver metabolic damage caused by HFD. Keywords: Nonalcoholic fatty liver disease, Celastrol, Sirt1, Lipid metabolism, Chronic inflammation, Oxidative stress